Jembatan Kurikulum: Inklusi dan Pembelajaran Bahasa Arab dalam Konteks Multikultural - Aziz, Muhammad Tareh; Hasan, Laili Mas Ulliyah; Adhimah, Syifaul (Journal of Practice Learning and Educational Development, 2024)
This study explores the implementation of inclusive Arabic language learning in a multicultural context, which includes all four language skills: listening, speaking, reading, and writing. This research uses a qualitative approach by collecting data through classroom observations, interviews with teachers, and analysis of curriculum documents. The findings show that the integration of inclusion values ​​and multiculturalism in the curriculum provides a basis for developing learning strategies that take into account student diversity. With a holistic approach, learning Arabic can be a bridge to strengthen intercultural relations and promote cross-cultural understanding among students from diverse backgrounds. The practical implications of this research underscore the need for learning approaches that are adaptive and responsive to students' needs by considering their multicultural context.